2020
DOI: 10.3389/fmed.2020.614482
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Renal Involvement in Primary Sjögren's Syndrome: A Meta-Analysis

Abstract: Background: Renal impairment is a critical complication in primary Sjögren's syndrome (pSS), resulting in chronic renal disease and even death. This meta-analysis was designed to find out the relevant factors of renal involvement in pSS.Methods: PubMed, EMBASE, Cochrane Library, Scopus, and Web of Science were systemically searched until August 30, 2019. Studies were selected according to inclusion criteria, and data was extracted by two researchers independently. The Newcastle-Ottawa Scale was applied for qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Prior studies have examined potential risk factors in pSS-RTA patients, encompassing demographics, clinical features, and laboratory parameters [13][14][15][16][17]. Nevertheless, there has been a lack of studies speci cally tackling pSS-RTA and developing a model that integrates multiple laboratory ndings into clinical decision-making.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies have examined potential risk factors in pSS-RTA patients, encompassing demographics, clinical features, and laboratory parameters [13][14][15][16][17]. Nevertheless, there has been a lack of studies speci cally tackling pSS-RTA and developing a model that integrates multiple laboratory ndings into clinical decision-making.…”
Section: Discussionmentioning
confidence: 99%
“…Jain et al [13] reported a lower incidence of dry eyes in pSS-RTA patients compared to those without RTA, with a similar rate of dry mouth occurrence. Conversely, a meta-analysis showed no signi cant correlation between renal involvement in pSS and anti-SSA antibodies, rheumatoid factor, dry eye syndrome, or labial salivary gland biopsy [14]. Synthesizing previous studies [13,[15][16][17], it is revealed that several factors are associated with pSS-RTA, including a younger age of onset, longer disease duration, subjective dry mouth, arthritis, EULAR disease activity index, decreased glomerular ltration rate, thyroid disease, anemia, elevated alkaline phosphatase levels, decreased albumin levels, increased erythrocyte sedimentation rate, anti-SSA and anti-SSB antibodies, and high gamma globulin levels.…”
Section: Introductionmentioning
confidence: 90%
“…Among these factors, positive anti-SSA and/or anti-SSB antibodies are often considered immunological parameters of disease activity and extraglandular involvement in pSS. Previous researches and meta-analysis showed that the presence of anti-SSA antibody [ 28 , 29 ] and anti-SSB antibody [ 30 ] were positively related to renal involvement, development or worse outcome of renal impairment in pSS. In our study, anti-SSA was observed to be positive associated with renal injury by multivariate analysis, which was also found in previous study showed antibodies anti-SSA and anti-SSB were associated with renal disease (particularly with TIN), and with poorer renal prognosis [ 6 , 28 ], suggesting that pSS patients warrant careful workup for renal function.…”
Section: Discussionmentioning
confidence: 99%
“…Renal involvement represents a quite common extra-glandular complication in SS patients with a prevalence ranging from 2% to 40% according to cohort analysed and diagnostic methods. Moreover, manifestations related to renal involvement are highly variable and several factors, as anti-SSB antibodies and early-onset disease, have been associated with higher risk of kidney involvement in these patients (80)(81)(82). Development of renal complication during disease course may affect patient prognosis and is associated with severe disease, systemic multiorgan involvement.…”
Section: S-8mentioning
confidence: 99%